Immune landscape and biomarkers for immuno-oncology in colorectal cancers - Jeong Mo Bae; Seung-Yeon Yoo; Jung Ho Kim; Gyeong Hoon Kang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Recent advances in immuno-oncology have increased understanding of the tumor immune microenvironment (TIME), and clinical trials for immune checkpoint inhibitor treatment have shown remission and/or durable response in certain proportions of patients stratified by predictive biomarkers. The TIME in colorectal cancer (CRC) was initially evaluated several decades ago. The prognostic value of the immune response to tumors, including tumor-infiltrating lymphocytes, peritumoral lymphoid reaction, and Crohn's-like lymphoid reaction, has been well demonstrated. In this review, we describe the chronology of TIME research and review the up-to-date high-dimensional TIME landscape of CRC. We also summarize the clinical relevance of several biomarkers associated with immunotherapy in CRC, such as microsatellite instability, tumor mutational burden, POLE/POLD mutation, consensus molecular subtype, and programmed death-ligand 1 expression.